An investigation into the financial challenges affecting the success of entrepreneurs in South Africa - Nkwinika, Eugine; Olufemi Akinrinde, Olawale (Technology audit and production reserves, 2023)
The object of this study is the financial difficulties that impacted the success of business owners in Hatfield, Gauteng province, South Africa. Compared to a global failure rate of 50 %, five out of every seven entrepreneurs in Hatfield, South Africa fail during the first year of operation. This study aimed at looking into the relationship between entrepreneur failure and financial literacy. The methodology employed in this study is interpretive philosophy-based qualitative research. An ethnographic research technique was also used to analyze the current economic condition of business owners in Hatfield. The population was sampled using non-probability purposive sampling techniques. Semi-structured interviews were used to gather the study’s leading source of data. The primary research results are thematically examined while also considering the secondary sources. Eliminating financial and liquidity constraints was listed as a goal of financial literacy. Findings garnered revealed that financial, liquidity and credit restrictions are the primary causes of business failures in Hatfield. The lack of financial resources for new businesses in Hatfield, as revealed, prompted several liquidity issues in Hatfield, and further lowers the growth rate of Hatfield businesses. It was discovered that Hatfield’s entrepreneurs usually experienced premature failure due to inadequate financial education and training. Impliedly, Hatfield business owners possessed poor cash management, defaulting on loan payments due to lack of financial education. Conversely, only few entrepreneurs and business owners in Hatfield, South Africa possess financial literacy competence with the necessary skills needed to better analyze their financial statements appropriately and increase profitability of their business. The practical implication of this finding is that, most entrepreneurs have high possibility to experience premature business liquidity when they have low or no financial literacy.